PANJI DALAM TRADISI SENI PERTUNJUKAN: Alih Estetika dari Keraton Merasuki Estetika Kerakyatan - Prakosa, Rohmat Djoko (LP2M ISBI Bandung, 2023)
Panji in the performing arts tradition has a big role. The diversity of forms and types of performances expresses the Panji cycle on the theme of wandering/wandering patriotic, romantic. There is an aesthetic transfer from palace aesthetics to popular aesthetics, research into this aesthetic transfer needs to be carried out to obtain aesthetic diversity. So it is necessary to explore the variants formed by local and folk traditions. To explore Panji’s cultural diversity in performing arts, a literature study is needed to approach Panji from the perspective of performing arts history. Direct observation of the forms and types of Panji performances, and observation of audio-visual documents, portraits and social media broadcasts about Panji. The results of the literature study and observations made can be described as the story of Panji in various forms of performance aesthetic expression. A variety of aesthetic performances of theatre, music, dance and visual aesthetic expressions. Broadly speaking, the aesthetics of the story of Panji is told in a classical aesthetic that is developed as a palace tradition and is embodied in the populist aesthetics that are spread across various areas of local populist culture. Keywords: Panji, tradition, aesthetics, performance